A STRATEGI SISTEM INFORMASI MANAJEMEN DALAM PELAYANAN ADMINISTRASI KESISWAAN - Puspita Sari, Intan; Hidayati, Dian (Universitas Islam Negeri Alauddin Makassar, 2023)
In a globalization era that is marked by advancements in information technology, the integration of technology in learning systems and processes is crucial, especially in the context of educational institutions. This research aimed to describe and analyze management information system strategies in student administration services at SD Muhammadiyah Mlangi by using data analysis techniques assisted by Atlas.ti 8 software, with qualitative research methods and a case study approach. The results showed that SD Muhammadiyah Mlangi successfully integrated technological advances in administrative services to students, involving the use of technology and internet networks with the active involvement of teachers. Thus, quality education services are created. This research is expected to provide a comprehensive overview of the strategies used by SD Muhammadiyah Mlangi and the positive impact of the implementation of these strategies on the quality of education provided by the school, providing valuable insights to face the challenges of globalization in the field of education.